AN APPRAISAL OF OAU AS A TOOTHLESS BULLDOG AND ITS TRANSFORMATION TO AFRICAN UNION, 1963-2002 - MICHAEL, EDIAGBONYA (Innovare Journal of Social Sciences, 2023)
This paper examines the Organization of African Unity (OAU) as a toothless bulldog. The genesis, charter, and achievements of the Organization also came to focus. It assesses the transformation of OAU to African Union in 2002. The data were obtained from primary and secondary sources. Oral interview constituted the primary sources while books, newspapers, journals, theses, and desertion serves as secondary sources. It was found that OAU which was established in 1963, transformed into African Union in 2002. It was also found that the non-interference of OAU in the internal affairs of member states was a serious challenge. It was demonstrated that the OAU was clearly a toothless bulldog and a talking club of African leaders. In conclusion, it was noted that the transformation of OAU to AU was a step in the right direction because of the monumental failure of OAU to deliver on its mandate.